Dynamics of sliding contacts in mine slow – speed railway transportation - Miedziński, B.; Dzierżanowski, W.; Wandzio, J.; Grechanyuk, N.; Shoffa, V.N. (Электрические контакты и электроды, 2012)
Paper presents and discussed results of investigation as well as simulation of a sliding contact dynamics when used in a slow – speed railway of a copper mine transportation.